Aproximação de campo fraco e ondas gravitacionais - Santos, Josianne Catarina de Sousa Rodrigues dos (2019)
In 1915, the general relativity theory (TRG) was proposed by Albert Einstein. This theory is a generalization of the relativity principle of motion for systems where include gravitatio nal field and is based on a three postulates. For construction of the TRG, is required to use mathematical tools of curved space, no longer restricted to the Euclidean space. A way to do this is through algebra tensor, however, it is in the topology study that this study is most com plete. After the construction of TRG, Einstein predicted the existence of gravitational waves, it was finally detected on September 14, 2015, in the USA, one hundred years after the predict. This waves has specific characteristics, but with some similarities with electromagnetic waves. Therefore, this work show the construction of this theory, and the motivation for this was the detected of the gravitational waves in 2015, and this work finishing with the interaction the gra vitational waves with the matter and its polarization